معوقات استخدام الإنترنت لأغراض البحث العلمي من وجهة نظر طلبة الدراسات العليا دراسة ميدانية في كليتي التربية والعلوم في جامعة دمشق - محمد محمود علي; محمد وعد (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف هذا البحث إلى تعرف المعوقات التي تواجه طلبة الدراسات العليا عند استخدامهم الإنترنت لأغراض البحث العلمي وذلك من خلال الإجابة عن الأسئلة التالية : 1- ما المعوقات التي تواجه طلبة الدراسات العليا في في أثناء استخدام الإنترنت لأغراض البحث العلمي؟ 2- هل يوجد اختلاف بين إجابات طلبة الدراسات العليا فيما يتعلق بتحديدهم للمعوقات التي تواجههم عند استخدام الإنترنت لأغراض البحث العلمي تبعاً لكل من متغير الجنس، التخصص الدراسي، المستوى الدراسي( سنة أولى، سنة ثانية، دكتوراه)؟ اعتمد البحث المنهج الوصفي التحليلي باستخدام استبانة محكمة مكونة من ( 30) عبارة موزعة على ثلاثة مجالات،وزعت على عينة من طلبة الدراسات العليا قوامها (555) طالباً وطالبةً.وتوصل البحث إلى النتائج التالية: 1- معظم عبارات الاستبانة شكلت معوقات لطلبة الدراسات العليا عند استخدام الإنترنت لأغراض البحث العلمي بدرجة كبيرة ومتوسطة. 2- لم توجد فروق ذات دلالة إحصائية بين متوسطات إجابات طلبة الدراسات العليا في جامعة دمشق المتعلقة بتحديدهم لدرجات معوقات استخدام الإنترنت في البحث العلمي تعزى لمتغيري الجنس والتخصص الدراسي، وتبين وجود فروق ذات دلالة إحصائية بين متوسطات إجابات الطلبة المتعلقة بتحديدهم لدرجات معوقات استخدام الإنترنت في البحث العلمي تعزى لمتغير المستوى الدراسي ولصالح طلبة الدكتوراه. This research aims at identifying the obstacles facing graduate students when they use the Internet for the purposes of scientific research by answering the following questions: 1 - What are the obstacles faced by graduate students while using the Internet for research purposes? 2 - Is there a difference between the answers of graduate students as regardschallenging the obstacles they face when using the Internet for the purposes of scientific research? The research employs descriptive analytical method by using questionnaires composed of (30) distributed over three areas, the research found the following results: 1 - Most resolution phrases constituted obstacles to graduate students when using the Internet for the purposes of scientific research substantially and medium. 2 - There are no statistically significant differences between the mean of graduate students’ answers at the University of Damascus concerning their challenge for degrees of constraints of Internet use in scientific research; there are significant differences between the mean of students’ answers concerning their challenge for degrees of constraints of Internet use in scientific research due to the academic variable level in favor of Ph.D. students.